2017
DOI: 10.1074/jbc.m117.775528
|View full text |Cite
|
Sign up to set email alerts
|

An antidote approach to reduce risk and broaden utility of antibody-based therapeutics

Abstract: Antibody therapeutics offer effective treatment options for a broad range of diseases. One of the greatest benefits of antibody therapeutics is their extraordinarily long serum half-life, allowing infrequent dosing with long-lasting effects. A characteristic of antibodies that drives long half-life is the ability to interact with the recycling receptor, FcRn, in a pH-dependent manner. The benefit of long half-life, however, carries with it liabilities. Although the positive effects of antibody therapeutics are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Thus, these substitutions might not change the antibody's affinity for FcγRIIIa of IgG2_YLA. In relation to FcRn binding, it has been reported that residue IgG1 L309 is included in the key contact positions on the Fc region with FcRn . However, compared to that of IgG2, IgG2_YLA has almost the same KD with FcRn.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these substitutions might not change the antibody's affinity for FcγRIIIa of IgG2_YLA. In relation to FcRn binding, it has been reported that residue IgG1 L309 is included in the key contact positions on the Fc region with FcRn . However, compared to that of IgG2, IgG2_YLA has almost the same KD with FcRn.…”
Section: Discussionmentioning
confidence: 99%
“…Although some of these approaches, mostly biotin–streptavidin pair, have been tested in nuclear imaging and therapy in patients, there is still a substantial risks of immunogenicity, , as well as suboptimal clearing efficiency. More recently, several interesting clearing approaches to block FcRn recycling by in vivo PEGylation of the Fc portion or by anti-FcRn antibody have been reported. However, these approaches still retain IgG in tissues, require introduction of non-natural amino acids into the antibody sequence, or interfere with metabolism of natural immunoglobulins.…”
mentioning
confidence: 99%